Local Wisdom and Sustainable Fisheries Management in Aceh Province: Customary Law Perspective - Fikri, Fikri; Idris, Idris; Catur Siswandi, Ahmad Gusman; Imamulhadi, Imamulhadi (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2026)
Fisheries resources, especially capture fisheries, are inherently open access; however, without proper management or when exploited excessively, they risk depletion or even extinction. At the global level, fish consumption continues to rise, while production from capture fisheries has shown a steady decline. This situation can be interpreted as evidence of widespread overfishing of capture fisheries resources. If this trend persists, it will pose a serious threat to global food security, particularly within the fisheries sector. Aceh Province is a maritime region surrounded by seas and possesses significant potential for capture fisheries. Nevertheless, illegal, unreported, and unregulated (IUU) fishing presents a serious risk to the sustainability of fisheries resources in the area. At the same time, Acehnese fishing communities are supported by a traditional maritime institution known as Panglima Laot, which, grounded in local wisdom, has played an important role in preserving the sustainability of fisheries resources up to the present. This article examines the role of local wisdom in sustainable fisheries management in Aceh Province. The study employs a normative legal research approach, with data collected by means of an analysis of legal documents. The findings indicate that Aceh Province holds the authority to implement sustainable fisheries management based on both national legislation and Aceh Qanun governing the sector. In addition, fisheries management is conducted through the customary institution of Panglima Laot, which has its own organizational structure and regulatory framework, particularly in overseeing fishing activities at sea. The local wisdom values embedded in this institution include justice, solidarity, and sustainability. In this regard, Panglima Laot has made a significant contribution to resolving conflicts within fishing communities.